(untitled) (Patan Pragya, 2020)
This article examines the broader political and economic historical contexts within which the centralTarai was incorporated into the Nepali state since the so called national unification in the second half of the eighteenth century and subsequently how the relationship between the successive rulers and the Madhesi people has been remaining confrontational. Based on the data drawn from the historiography of Nepal vis-à-vis the central Tarai and the perceptions and experiences of Madhesi people regarding their identity issues, it is argued that historically evolving geopolitics of the centralTarai and the contingent Madhesis’ self-consciousness have provided the cause and context for organizing and mobilizing them for the assertion of distinct collective identity. The strategic geopolitical location and significant cultural distinction and economic strength of the central Tarai provided Madhesi people a leverage in the struggle for the recognition of their distinct identity.